2001
DOI: 10.1063/1.1353809
|View full text |Cite
|
Sign up to set email alerts
|

Superhardness effects of heterostructure NbN/TaN nanostructured multilayers

Abstract: Although superhardness effects have been extensively investigated for epitaxial ceramic nanomultilayer films with the same crystal structures in the last decade, those for multilayers with different crystal structures have been seldom studied. In this article, NbN/TaN nanomultilayers have been designed and deposited by reactive magnetron sputtering. The results showed that the crystal structures of NbN and TaN are face-centered cubic and hexagonal in superlattice films, respectively, and the lattice plane (111… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…For the case of the NbN/TaN ncnl(s) [48], the analysis of the elastic modulus difference only accounts for an enhancement of 7 GPa where a N20 GPa enhancement is measured. The effect of coherency stress fields [49,55,56] can be used to (more than) account for the additional increase of 17 GPa assuming that the misfit strain (N) equals approximately one-half the 3.2% lattice mismatch between (111) NbN and (110) TaN . In another case for AlN/VN [50], consideration of coherency strain effects are necessary to account for the increases in hardness of the ncnl(s).…”
Section: Discussionmentioning
confidence: 99%
“…For the case of the NbN/TaN ncnl(s) [48], the analysis of the elastic modulus difference only accounts for an enhancement of 7 GPa where a N20 GPa enhancement is measured. The effect of coherency stress fields [49,55,56] can be used to (more than) account for the additional increase of 17 GPa assuming that the misfit strain (N) equals approximately one-half the 3.2% lattice mismatch between (111) NbN and (110) TaN . In another case for AlN/VN [50], consideration of coherency strain effects are necessary to account for the increases in hardness of the ncnl(s).…”
Section: Discussionmentioning
confidence: 99%
“…According to Li and co-workers [95], this superlattice system shows both a superlattice effect in hardness variation and a supermodulus effect (increase of the elastic modulus with decreasing bilayer modulation period) with maximum values both for the hardness and the elastic modulus achieved at a modulation period of 1 nm. Epitaxial stabilization, sometimes accompanied by superlattice effects, was observed in a variety of other nitride multilayer systems, for example in TiN/TaN [97][98][99], TiN/MoN [7], NbN/TaN [100], or in combination with CN x [7] or even oxynitride materials [101]. Söderberg et al [102,103] reported the successful epitaxial stabilization of cubic silicon nitride in TiN/SiN x superlattice films at a SiN x layer thickness of 0.3 nm.…”
Section: Stabilization Effects In Nitride Multilayer Systemsmentioning
confidence: 99%
“…This superhardness effect of multilayers mainly results from the following two reasons: first, since the coherent interface is formed by the epitaxial growth of AlN and TiN, there exists an alternating strain field in the multilayers due to lattice misfit, which can block the motion of dislocations and induce the strengthening of multilayers [2,4]; second, the formation of metastable c-AlN can increase the mechanical properties of multilayers. Previous experimental results [5,18] have shown that when h-AlN transforms to cubic structure, the volume of AlN decreases 18% and its elastic modulus increases from 205 to 270 GPa.…”
Section: Superhardness Effect Of Nanomultilayersmentioning
confidence: 99%
“…Research on multilayers that consist of two nanoscalelayered materials has drawn a lot of interest [1][2][3][4]. It has been shown that multilayers that consist of two materials with the same crystal structure and close lattice constant may form coherent epitaxial growth.…”
Section: Introductionmentioning
confidence: 99%